A case of Ignatzschineria bacteraemia in an unconscious man from the Netherlands. Issue 3 (25th June 2016) - Heddema, Edou; Janssen, Frank; Westreenen, Harro van
Abstract : Introduction: Ignatzschineria species were previously known as Schineria species and are well known inhabitants of the larvae of the parasitic fly Wohlfahrtia magnifica . Case presentation: We report a case of Ignatzschineria species bacteraemia in a Dutch patient with a wound infested with maggots. Conclusion: In the past, these bacteria have been isolated from Wohlfahrtia magnifica, a fly not indigenous to The Netherlands. Other fly larvae such as the blowfly larvae probably infested the wound and harboured this Ignatzschineria strain which subsequently caused this bacteraemia. A two-week course of amoxicillin/clavulanic acid was given with good clinical response.